1999
DOI: 10.1108/13552559910274499
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing small business start‐ups

Abstract: Sheds light on the process leading to new enterprise formation and identifies the impact of some selected demographic variables on business start‐ups. In contrast to traditional research methodologies, this study used a new and more comprehensive approach to survey entrepreneurial intention. It studied both those who actually set up a new business and those “nascent entrepreneurs” who abandoned their idea prior to trading. The findings of an empirical analysis of 93 such entrepreneurs are presented. Using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
122
3
24

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(182 citation statements)
references
References 37 publications
16
122
3
24
Order By: Relevance
“…In entrepreneurship, the relationship between the environment and the organization is a newly developed approach. Supporters of this approach believe that the entrepreneurial personality approach has reached its end and has a small contribution to the understanding of the new company (Mazzarol, Volery, Doss, & Thein, 1999). It is worth noting that the behavioral theories have a focus on environmental factors.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In entrepreneurship, the relationship between the environment and the organization is a newly developed approach. Supporters of this approach believe that the entrepreneurial personality approach has reached its end and has a small contribution to the understanding of the new company (Mazzarol, Volery, Doss, & Thein, 1999). It is worth noting that the behavioral theories have a focus on environmental factors.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…According to the literature and interactive model, it can be concluded that, in general, the majority of research on factors affecting the business, environmental factors and individual factors have been considered as important and influential and play a central role in the process of creating business (Mazzarol et al, 1999). However, a number of researchers have attempted to ensure that each of these factors contributed effectively to the creation of small and medium enterprises, but it should also be kept in mind that these factors can contribute to business creation if considered together.…”
Section: A Proposed Conceptual Model For Smsesmentioning
confidence: 99%
“…According to Kuckertz and Wagner (2010) [6], the main literature on SE has often focused on the environmental aspects of entrepreneurship [8][9][10][11][12][13][14][15], while other investigations in this area have mainly dealt with the social dimension of SE [16][17][18]. The influence of socioeconomic status, religion and personality attributes on SE have all been considered to varying degrees [19]. Accordingly, Sinha (1996) [20], Mazzarol et al (1999) [19] and Kristiansen et al (2003) [21] identified demographic factors that have considerably impact the success of entrepreneurial performance.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of socioeconomic status, religion and personality attributes on SE have all been considered to varying degrees [19]. Accordingly, Sinha (1996) [20], Mazzarol et al (1999) [19] and Kristiansen et al (2003) [21] identified demographic factors that have considerably impact the success of entrepreneurial performance. Moreover, a review by Hall et al (2010) [22] reveals the extant of the …”
Section: Introductionmentioning
confidence: 99%
“…Further, Mazzarol et al (1999) and also Skokic and Morrison (2011) suggest that the owner-manager's socio-economic characteristics such as age, gender and education level also form a part of the obstacles that have a considerable effect on entrepreneurial intention and business performance of SMEs. Tourism SMEs have to face many challenges just like other SMEs elsewhere are facing such as, a shortage of financial resources, lack of management and marketing skills, lack of industry expertise and strategic vision (Beaver et al, 1998;Boer 1998;Dewhurst and Horobin 1998;Friel, 1998;Wanhill, 1998;Webster, 1998;Shaw and Williams, 2001;Augustyn, 2013;Thomas and Augustyn, 2007).…”
Section: Review Of Literaturementioning
confidence: 99%